Figures of the Future : Latino Civil Rights and the Politics of Demographic Change - Rodríguez-Muñiz, Michael (Book collections on Project MUSE., 2021)
This book takes an in-depth look at how U.S. Latino advocacy groups are using ethnoracial demographic projections to bring about political change in the present.